Structural effects of inosine substitution in telomeric DNA quadruplex - Zheng, Ya Ying; Dartawan, Ricky; Wu, Yuhan; Wu, Chengze; Zhang, Hope; Lu, Jeanne; Hu, Ashley; Vangaveti, Sweta; Sheng, Jia (Frontiers in Chemistry, 2024)
The telomeric DNA, a distal region of eukaryotic chromosome containing guanine-rich repetitive sequence of (TTAGGG)n, has been shown to adopt higher-order structures, specifically G-quadruplexes (G4s). Previous studies have demonstrated the implication of G4 in tumor inhibition through chromosome maintenance and manipulation of oncogene expression featuring their G-rich promoter regions. Besides higher order structures, several regulatory roles are attributed to DNA epigenetic markers. In this work, we investigated how the structural dynamics of a G-quadruplex, formed by the telomeric sequence, is affected by inosine, a prevalent modified nucleotide. We used the standard (TTAGGG)n telomere repeats with guanosine mutated to inosine at each G position. Sequences (GGG)4, (IGG)4, (GIG)4, (GGI)4, (IGI)4, (IIG)4, (GII)4, and (III)4, bridged by TTA linker, are studied using biophysical experiments and molecular modeling. The effects of metal cations in quadruplex folding were explored in both Na+ and K+ containing buffers using CD and UV-melting studies. Our results show that antiparallel quadruplex topology forms with the native sequence (GGG)4 and the terminal modified DNAs (IGG)4 and (GGI)4 in both Na+ and K+ containing buffers. Specifically, quadruplex hybrid was observed for (GGG)4 in K+ buffer. Among the other modified sequences, (GIG)4, (IGI)4 and (GII)4 show parallel features, while (IIG)4 and (III)4 show no detectable conformation in the presence of either Na+ or K+. Our studies indicate that terminal lesions (IGG)4 and (GGI)4 may induce certain unknown conformations. The folding dynamics become undetectable in the presence of more than one inosine substitution except (IGI)4 in both buffer ions. In addition, both UV melting and CD melting studies implied that in most cases the K+ cation confers more thermodynamic stability compared to Na+. Collectively, our conformational studies revealed the diverse structural polymorphisms of G4 with position dependent G-to-I mutations in different ion conditions.